Mobility aspirations and indigenous belonging among Chakma students in Dhaka. Issue 4 (1st October 2016) - Visser, Jacco; Gerharz, Eva
ABSTRACT: In recent decades, indigenous people from the Chittagong Hill Tracts (CHT) in South-east Bangladesh have experienced increased social and spatial mobility. This article investigates how indigenous students from the CHT region who have migrated to Dhaka redefine indigenous belonging. By highlighting the juxtaposition of different forms of mobility (physical and social) the paper responds to a recent trend which has only rarely been the subject of scholarly enquiry. In particular, it examines the experiences of mobility of individual students and explores the ways in which these students justify their quest for higher education to fulfil their aspirations for a better future. The paper also reveals the obstacles students experience in their everyday lives, mainly in the form of stereotypical, often racist talk. It discusses the structural disadvantages indigenous students face as members of ethnic minorities as well as the strategies employed by the students to counter them. Furthermore, the paper illustrates how indigenous students negotiate urban lifestyles and redefine modernity and indigeneity simultaneously and how migrants face exclusion based on static interpretations of people from the CHT as put forward in mainstream discourses as well as by transnational indigenous activist networks. These lead to feelings of alienation between indigenous students and their Bengali Bangladeshi peers, leaving students to increasingly draw on indigenous networks to achieve mobility.